ANALYSIS OF THE EFFECT OF LAND-USE CHANGES ON THE CARRYING CAPACITY OF THE CIKERUH SUB-WATERSHED USING THE SWAT HYDROLOGICAL MODEL - Riezcy Cecilia Dewi; Asep Suheri; Yayat Hidayat (University of Lampung, 2022)
Cikeruh Sub-Watershed is an area that has occurred a lot of land-use conversions, for residential and industrial, especially in the Jatinangor and Rancaekek districts. The annual sediment rate that occurred in 1994-2001 reached 100 tons/km2. Characteristics of the biophysical carrying capacity of Cikeruh Sub-Watershed need to be studied to provide an overview of the Sub-Watershed conditions. Using the SWAT model in this study is very effective and efficient in predicting the impact of land management practices on the carrying capacity of the Cikeruh Sub-Watershed. The purpose of this study is: (1) to identify biophysical characteristics, (2) determine the carrying capacity of Sub-Watershed, and (3) provide recommendations for the best land-use scenario in Cikeruh Sub-Watershed. The parameters analyzed are land and hydrological characteristics based on Permenhut Number P.61/Menhut-II/2014 about Monitoring and Evaluation of Watershed Management. The statistical analysis shows that the performance level of the model in the calibration and validation process is satisfactory with the values of NSE (0,57) and R2 (0,62) in the calibration process and NSE (0,46) and R2 (0,51) in the validation process. The biophysical characteristics of the Cikeruh Sub-Watershed have good criteria are KRA, KAT, and IPA, while poor criteria are PLK, PPV, erosion index, sediment loads, and flood. The carrying capacity of the Cikeruh Sub-Watershed is the moderate criteria. The best scenario to solve these problems is scenario 2 by converting agriculture to the forest by 17%, rice to the forest by 3%, and rice to agriculture by 7%.